Pengaturan Perjanjian Kerja Waktu Tertentu (PKWT) Berdasarkan Peraturan Pemerintah Nomor 35 Tahun 2021 Tentang Perjanjian Kerja Waktu Tertentu, Alih Daya, Waktu Kerja dan Waktu Istirahat, dan Pemutusan Hubungan Kerja - Ria Sintha Devi (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses how to implement fixed-term work agreements (PKWT) based on Government Regulation (PP) Number 35 of 2021 concerning Fixed-Time Work Agreements, Outsourcing, Working Time and Rest Time, and Termination of Employment Relations. This type of research is normative law and the nature of this research is descriptive analysis. The data collection technique was carried out by means of library research, the data used is secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. Research results This method uses qualitative analysis which will later be arranged systematically to answer the problems that have been formulated. Regulations regarding PKWT itself have been specifically regulated in Law no. 13 of 2003 (Employment Law), but along with the enactment of Law no. 10 of 2020 (Job Creation Law) which was later amended by Law no. 06 of 2023, several provisions in the Employment Law have undergone changes. However, the rules regarding the validity of a work agreement have not changed as regulated in article 52 of the Manpower Law. The Specific Time Work Agreement (PKWT) underwent several significant changes after the enactment of Law no. 6 of 2023 which is a stipulation from Perppu no. 2 of 2022 concerning Job Creation, as well as Government Regulation (PP) no. 35 of 2021. In PKWT, contract workers have a working period specified in the agreement, and the Job Creation Law introduces new provisions regarding compensation for contract workers when the work period ends, different from the previous Employment Law. Job Creation Law no. 6 of 2023 also extends the duration of PKWT, clarifies the types of work that can be tied to PKWT, and adds rules regarding non-permanent work. The PKWT extension provisions, which were previously limited to three years, can now be extended to five years or until the work is completed. One other important difference is that PKWT must be in writing, and if not, it automatically changes to PKWTT.